META-ANALYSIS OF THE EFFECT OF THE USE OF JIGSAW TYPE COOPERATIVE MODEL ON STUDENT LEARNING OUTCOMES IN LEARNING NATURAL SCIENCE IN JUNIOR HIGH SCHOOL AND PHYSICS IN SENIOR HIGH SCHOOL - Atika Dwi Maharani Zuler; - Desnita; - Murtiani; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2021)
This meta-analysis study aims to analyze the effect size of the use of the jigsaw cooperative model based on education level, material units, and aspects of learning outcomes including knowledge, attitudes, and skills.  The research method used is a meta-analysis of 25 articles that have been published in various national and international journals and proceedings. The results of this study are as follows: (1) The use of the type cooperative model jigsaw in improving learning outcomes based on education level, more have an effect on the high school level; (2) The use of the jigsaw type cooperative model in improve learning outcome based on material units, more influential on units optics and thermodynamics material for high school level and affect the unit thermodynamics and vibration & wave materials for junior high school level; (3) The use of the type cooperative model jigsaw in improving learning outcomes has an effect on aspects of attitude, knowledge, and skills.